2012
DOI: 10.1007/s00330-012-2556-5
|View full text |Cite
|
Sign up to set email alerts
|

Radioembolisation with 90Y-labelled resin microspheres in the treatment of liver metastasis from breast cancer

Abstract: (90)Y RE is effective in the treatment of liver metastases from breast cancer. We demonstrated a relevant survival and encouragingly high response rate in patients with treatment-refractory disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 15 publications
4
44
0
1
Order By: Relevance
“…Radioembolization is known to be a useful tool in treating primary and secondary tumors of the liver [8]. In particular, several published papers reported that 90 Y radioembolization can be effective and safe in hepatic NET [6].…”
Section: Discussionmentioning
confidence: 99%
“…Radioembolization is known to be a useful tool in treating primary and secondary tumors of the liver [8]. In particular, several published papers reported that 90 Y radioembolization can be effective and safe in hepatic NET [6].…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies all showed positive results with SIRT in this setting, none reported on the combination of SIRT with other therapies (10,(103)(104)(105)(106)(107)(108). Experienced SIRT teams regularly treating breast cancer metastases advise caution in total activity delivered in those patients with several years of chemotherapy exposure.…”
Section: Metastatic Breast Cancermentioning
confidence: 99%
“…Four studies reported the median OS of BRCLM after RE ranging from 11.5 months to 14.2 months (table 1). Mild to moderate post-embolization syndrome of nausea, vomiting, fever and mild right upper quadrant pain occurred in almost all patients whereas severe toxicities like grade 1 to 3 gastrointestinal toxicities, stomach ulcers and sever hepatic failure were rare [36,37,38,39]. …”
Section: Secondary Liver Cancers Other Than From Colorectal Cancersmentioning
confidence: 99%